Optimalisasi Penegakan Hukum Pidana Terhadap Tindak Pidana Perikanan (Studi Perbandingan Hukum Pidana Di Bidang Perikanan) - Astuti Nur Fadillah; Muhammad Insan Anshari Al Aspary (SASI, 2020)
For the fisheries sector in Indonesia, Law No. 31 of 2004 Jo. Law No. 45 of 2009 concerning Fisheries and in the Philippines the 1998 Philippine Fisheries Code applies, which is a regulation governing prison administration. Indonesian fisheries law has not yet enacted a ban on rare and endangered species. The Philippine fisheries law does not yet impose legal sanctions to cancel permit documents. The formulation of an emergency prison sentence or a Philippine fisheries law fine is relatively heavier than Indonesia. For the concept of accountability of the court by the two countries still imposes court responsibility only on corporate management. Law enforcement in the field of fisheries in Indonesia and the Philippines can be more effective on the prohibition of certain activities or activities related to liability related to relationships that can be accounted for, so that they can be accounted for in the right way, to help and overcome problems related to fisheries.